Meningkatkan prestasi belajar matematika siswa kelas XII TKJ A SMKN 3 Tabanan melalui penerapan pembelajaran berbasis masalah dengan teknik diskusi kelompok - I Gede Budiarsa (Indonesian Journal of Educational Development, 2020)
This research was conducted at Tabanan State Vocational School 3 in Class XII TKJ A, where the ability of students for Mathematics material was quite low. The purpose of writing this Classroom Action Research is to find out whether "The Implementation of Problem Based Learning Models with Group Discussion Techniques Can Improve Learning Achievement in Derivatives Function of Students of Class XII TKJ A SMK Negeri 3 Tabanan Even Semester 2017/2018 Academic Year". The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study are the application of problem-based learning models with group discussion techniques can improve student achievement. This is evident from the results obtained increased from the initial average of 38.76 in the first cycle the average rose to 47.35, this means an increase of 8.59 (22.162%) and in the second cycle the average increase again is 84.71, means an increase of 37.36 (96.388%). In addition to an increase in learning achievement that can be seen from the test of learning outcomes, it turns out that an increase in learning achievement can also be seen from the results of the group discussions they did both in Cycle I and in Cycle II. In the discussion they have tried to solve the problems given by the teacher in each cycle. Achievements in Cycle I have not met the demands of the study, because they have not been in accordance with the proposed indicators of success, thus this study continues for one more cycle, with the hope that the authors would like to see developments that occur in Cycle II. The conclusion obtained from this study is the Implementation of Problem-Based Learning Models with Group Discussion Techniques Can Improve Learning Achievement in Derivatives Function of Grade XII Students of TKJ A SMK Negeri 3 Tabanan Even Semester 2017/2018 Academic Year. This can be seen from the increase in achievements from the initial achievements, the achievements in Cycle I even though they have not met the demands of the study, and there is an increase in Cycle II, which in Cycle II is in accordance with the demands of research based on the proposed indicators of success. And if we see from the results of the discussion it is clear there is an increase in the results of the discussion from Cycle I to Cycle II, meaning that this shows that students have progressed in solving the problems given by the teacher. So the expected goals of this research have been achieved, so that this research is not continued. Penelitian ini dilaksanakan di SMK Negeri 3 Tabanan di Kelas XII TKJ A semester genap tahun pelajaran 2017/2018 pada mata pelajaran matematika pokok bahasan turunan fungsi. Dari hasil penelitian pendahuluan didapatkan data bahwa prestasi belajar matematika kelas XII TKJ SMK Negeri Tabanan masih rendah. Tujuan penulisan penelitian ini adalah untuk meningkatkan prestasi belajar matematika siswa melalui penerapan pembelajaran berbasis masalah dengan teknik diskusi.Metode pengumpulan datanya adalah tes prestasi belajar. Metode analisis datanya adalah deskriptif. Hasil yang diperoleh dari penelitian ini adalah penerapan model pembelajaran berbasis masalah dengan teknik diskusi kelompok dapat meningkatkan prestasi belajar siswa. Ini terbukti dari meningkatnya rata-rata hasil belajar matematika pada penelitian pendahuluan 38,76 dan pada siklus I rata-ratanya naik menjadi 47,35, ini berarti terjadi kenaikan sebesar 8,59 (22,162 %) dan pada siklus II rata-ratanya menjadi 84,71, berarti terjadi kenaikan sebesar 37,36 (96,388%). Selain peningkatan prestasi belajar yang dapat dilihat dari tes hasil belajar ternyata peningkatan prestasi belajar juga dapat dilihat dari hasil diskusi kelompok yang mereka lakukan baik di siklus I maupun di siklus II. Dalam diskusi itu mereka telah berusaha menyelesaikan masalah-masalah yang diberikan guru pada setiap siklus. Kesimpulan yang diperoleh dari penelitian ini adalah Penerapan Pembelajaran Berbasis Masalah Dengan teknik Diskusi Kelompok Dapat Meningkatkan Prestasi Belajar Turunan Fungsi Siswa Kelas XII TKJ A SMK Negeri 3 Tabanan Semester Genap Tahun Pelajaran 2017/2018.